PECULIARITIES OF IMPLEMENTATION OF PUBLIC AND MANAGEMENT MECHANISMS OF DEVELOPMENT OF TERRITORIAL COMMUNITIES - Blazhivska Mar`yana (Theory and Practice of Public Administration, 2020)
The article describes the content of public and management mechanisms of development of united territorial communities, substantiates the reasons that have a destructive influence on the development process, suggests possible ways of solving actual problems. The purpose of the article is to summarize the conceptual foundations of public and management mechanisms of sustainable development for their further implementation in the context of decentralization of authorities and unification of territorial communities. Based on this purpose, the objectives of the study are: to determine the nature of different types of public and management mechanisms of development of united territorial communities; identify existing problems and possible ways to optimize the development process. The research methods in the work are: search on the available methodological and scientific literature with analysis of the found material, induction and deduction, clarification of cause and effect relationships, extrapolation, analysis of documentation and results of the researchers on the problem of the conducted research. The author believes that measures to strengthen the institution of local self-government and, accordingly, the empowerment of territorial communities and regions as a whole will help Ukraine to solve political, economic, social problems, first of all, to prevent manifestations of separatism and federalization. After all, a number of politicians are trying to manipulate the mood of the people and deliberately identify issues of decentralization and federalism. In the future, it is worth paying attention to possible ways of adapting and introducing the world experience of decentralization development in order to solve the existing problems, to amend the existing regulatory documents, to develop an algorithm for training applicants and elected managers of the united territorial communities.